Mental health services for minority ethnic children and adolescents - Malek, Mhemooda; Joughin, Carol (Child and adolescent mental health series., 2004)
Bringing together current research on mental health services for children from minority ethnic backgrounds, this much-needed resource provides guidance for both practice and policy. In the light of their interviews with child and adolescent mental health managers about their approaches to service development, the authors argue that the delivery of effective services can be achieved only by recognizing the diversity of cultures and individual needs of minority groups and encouraging more communication between service providers. They consider how ethnicity is defined, and how the field of mental.